2004
DOI: 10.1359/jbmr.040606
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Regulates Osteoclast Differentiation Through Its Transporter

Abstract: 5-HTT mediates antidepressant-sensitive clearance of 5-HT after its release into neural synapses. We found increased expression of 5-HTT in RANKL-induced osteoclast-like cells. Fluoxetine, an inhibitor of 5-HTT, reduced osteoclast differentiation but not activation. Reserpine, an inhibitor of 5-HT intracellular transport, potentiated differentiation. These results indicate a role for 5-HTT in osteoclast function and suggest that commonly used antidepressive agents may affect bone mass. Introduction:Interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
156
2
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(164 citation statements)
references
References 55 publications
3
156
2
3
Order By: Relevance
“…Receptors for serotonin have been found on osteoblasts [36], and several studies have reported that SSRIs induce a loss of bone mass in mice [35,37]. This is consistent with evidence from observational studies in humans, which report that SSRI use among older adults is associated with low BMD, independent of the effects of depression [38], and heightened BMD loss over time [39].…”
supporting
confidence: 74%
“…Receptors for serotonin have been found on osteoblasts [36], and several studies have reported that SSRIs induce a loss of bone mass in mice [35,37]. This is consistent with evidence from observational studies in humans, which report that SSRI use among older adults is associated with low BMD, independent of the effects of depression [38], and heightened BMD loss over time [39].…”
supporting
confidence: 74%
“…Bone is densely innervated, and the observation of direct contact of nerve fibers and bone cells strongly supports a role of innervation in bone cell functions. A number of neuromediators have also been detected by immunocytochemistry in nerve fibers in bone [18][19][20][21][22][23]. These studies suggest an important role of the neural system in regulating bone cell functions, and ultimately in influencing bone homeostasis.…”
Section: Introductionmentioning
confidence: 83%
“…Animal studies also indicated that serotonin may influence bone mass. Battaglino et al [27] demonstrated that mice injected daily with fluoxetine had increased bone formation. However, these effects are not observed in estrogen deficient animals; this finding suggests that the effect of antidepressants on bone metabolism may depend on sex steroids [28] .…”
Section: Introductionmentioning
confidence: 99%